Cyclitol metabolism is a central feature of Burkholderia leaf symbionts. (9th December 2022) - Danneels, Bram; Blignaut, Monique; Marti, Guillaume; Sieber, Simon; Vandamme, Peter; Meyer, Marion; Carlier, Aurélien
Abstract: The symbioses between plants of the Rubiaceae and Primulaceae families with Burkholderia bacteria represent unique and intimate plant–bacterial relationships. Many of these interactions have been identified through PCR‐dependent typing methods, but there is little information available about their functional and ecological roles. We assembled 17 new endophyte genomes representing endophytes from 13 plant species, including those of two previously unknown associations. Genomes of leaf endophytes belonging to Burkholderia s.l . show extensive signs of genome reduction, albeit to varying degrees. Except for one endophyte, none of the bacterial symbionts could be isolated on standard microbiological media. Despite their taxonomic diversity, all endophyte genomes contained gene clusters linked to the production of specialized metabolites, including genes linked to cyclitol sugar analog metabolism and in one instance non‐ribosomal peptide synthesis. These genes and gene clusters are unique within Burkholderia s.l. and are likely horizontally acquired. We propose that the acquisition of secondary metabolite gene clusters through horizontal gene transfer is a prerequisite for the evolution of a stable association between these endophytes and their hosts.